Biological Approaches for Remediation of Metal-Contaminated Sites - Pinto, AP (2017)
Environmental pollution by several heavy metals and metalloids is a severe problem worldwide, as soils became increasingly contaminated, posing a threat to ecosystems and ultimately to human health. Contamination derives from large scale urbanization and industrialization, threatening land ecosystems, surface and groundwater, as well as food safety and human health. Remediation strategies for heavy metal-contaminated sites are necessary to protect from their toxic effects and conserve the environment for future generations. Numerous physicochemical techniques have been adopted including excavation and deposition in landfills, thermal treatment, leaching and electro-reclamation. These techniques are fast but inadequate, costly, cause adverse effects on soil physical, chemical and biological properties, and may lead to secondary pollution. In fact, many of these approaches only change the problem from one form or place to another, and do not completely destroy the pollutants. There was an urgent need to develop new technologies which are cost-effective and eco-friendly. In this context, biological remediation has tremendous potential. It uses plants and microorganisms to remove or contain toxic contaminants and is considered as the most effective method because it is a natural process, environmentally-friendly, has a low cost, and wide public acceptance. The present chapter aims to provide a comprehensive review of some of the promising processes mediated by plant and microbes to remediate metal-contaminated environments. Some biological processes used for the decontamination of organic compounds will also be included because of their relevance and potential common use for both purposes.